1993
DOI: 10.1002/jlb.53.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous nitric oxide inhibits the synthesis of cyclooxygenase products and interleukin-6 by rat Kupffer cells

Abstract: Macrophage production of nitric oxide (.N = O) leads to considerable alterations of vital metabolic pathways in various target cells. The present study tested whether .N = O synthesis by Kupffer cells (KCs), the resident macrophages of the liver, interferes with the secretory function of these cells. As in other macrophage-type cells, the combination of lipopolysaccharide (LPS) and interferon-gamma (IFN-gamma) was a potent stimulus of .N = O synthesis by KC. Treatment with LPS and IFN-gamma also induced signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
0
4

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(111 citation statements)
references
References 34 publications
6
101
0
4
Order By: Relevance
“…Salvemini et al (34) have shown that injection of iNOS inhibitors into a rodent air pouch model (carrageenan-induced) blocked both iNOS and COX-2 activity in areas of inflammation. Our studies, in contrast, are similar to the studies by Stadler et al (35) and Swierkosz et al (36) that indicate that endogenous NO inhibits the synthesis of COX products as observed in rodent Kupffer cells and macrophages, respectively. This controversy may be due to the tissue-specific expression of NOS/COX-2 in various cell types, the difference in the pathophysiology of normal and OA-affected chondrocytes, and the influence of various other mediators in the microenvironment of the cartilage that may influence the production of NO and PGE 2 .…”
Section: Discussionsupporting
confidence: 93%
“…Salvemini et al (34) have shown that injection of iNOS inhibitors into a rodent air pouch model (carrageenan-induced) blocked both iNOS and COX-2 activity in areas of inflammation. Our studies, in contrast, are similar to the studies by Stadler et al (35) and Swierkosz et al (36) that indicate that endogenous NO inhibits the synthesis of COX products as observed in rodent Kupffer cells and macrophages, respectively. This controversy may be due to the tissue-specific expression of NOS/COX-2 in various cell types, the difference in the pathophysiology of normal and OA-affected chondrocytes, and the influence of various other mediators in the microenvironment of the cartilage that may influence the production of NO and PGE 2 .…”
Section: Discussionsupporting
confidence: 93%
“…27 The co-induction of COX-2 and iNOS has also been observed in studies in vitro of rat vascular smooth muscle cells, 28,29 glomerular mesangial cells, 7 murine macrophages, 30 rat islets of Langerhans, 31 human endothelial cells, 32 articular chondrocytes, 33 and rabbit hepatocytes 34 incubated with endotoxin and/or cytokines but not in similar studies of human fetal cell fibroblasts 6 or bovine aortic endothelial cells. 35 Proinflammatory cytokines known to be synthesized and released by T lymphocytes and macrophages during cardiac allograft rejection are probably responsible for induction of COX-2 in this situation.…”
Section: Discussionmentioning
confidence: 86%
“…In cultured bovine endothelial cells, NO or NO donor drugs have been shown to inhibit PGI 2 release by bradykinin (COX-1) 39 and to inhibit COX-2 induction and activity in rat Kupffer cells. 34 In contrast, however, NO and NO donor drugs have been shown to stimulate COX-1 and COX-2 activity in endotoxin-activated murine macrophages 6 and in vascular smooth muscle cells 28 and human endothelial cells. 39,40 Similarly, in the hydronephrotic model of renal inflammation, 22 in air-pouchinduced inflammation, 24 there is evidence that NO augments the activity of COX-1 and COX-2, leading to enhanced synthesis of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that in murine and human models these upper level fluxes of NO can be achieved in tissue. Inhibition of P450 and COX-2 have provided evidence that locally, high levels of NO can be achieved by inflamed liver cells [90][91][92] . Nitric oxide mediated inhibition of P450 may have important consequence under inflammatory conditions 93, 94 .…”
Section: The Concentration Range Of Endogenously Generated Nitric Oxidementioning
confidence: 99%